1998
DOI: 10.1093/jnci/90.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Expression in Benign Breast Epithelium and Breast Cancer Risk

Abstract: The overexpression of estrogen receptors in normal breast epithelium may augment estrogen sensitivity and hence the risk of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
211
4
13

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(248 citation statements)
references
References 14 publications
20
211
4
13
Order By: Relevance
“…The hypothesis is also supported by the results of several independent investigations that have shown an increase in the level of estrogen receptor ␣ expression as mammary histology progresses from normal to proliferative to carcinoma in situ and eventually invasive carcinoma 6,7 and by a report from a case-control study that the likelihood of breast cancer increases when there is overexpression of estrogen receptors in the normal epithelium. 8,9 Lastly, a role for normal breast tissue estrogen receptor ␣ expression in carcinogenesis is supported by the findings of an earlier investigation 10 showing significantly higher expression of estrogen receptor ␣ in the normal mammary tissue of Caucasian Australian women than in Japanese women in Japan. It may also be of importance that differences in estrogen receptor ␣ expression, in both the study by Lawson and colleagues 10 and the present study, are much more evident among postmenopausal than premenopausal women, in parallel with the higher international variability of breast cancer incidence in the former than in the latter group.…”
Section: Discussionmentioning
confidence: 72%
“…The hypothesis is also supported by the results of several independent investigations that have shown an increase in the level of estrogen receptor ␣ expression as mammary histology progresses from normal to proliferative to carcinoma in situ and eventually invasive carcinoma 6,7 and by a report from a case-control study that the likelihood of breast cancer increases when there is overexpression of estrogen receptors in the normal epithelium. 8,9 Lastly, a role for normal breast tissue estrogen receptor ␣ expression in carcinogenesis is supported by the findings of an earlier investigation 10 showing significantly higher expression of estrogen receptor ␣ in the normal mammary tissue of Caucasian Australian women than in Japanese women in Japan. It may also be of importance that differences in estrogen receptor ␣ expression, in both the study by Lawson and colleagues 10 and the present study, are much more evident among postmenopausal than premenopausal women, in parallel with the higher international variability of breast cancer incidence in the former than in the latter group.…”
Section: Discussionmentioning
confidence: 72%
“…Hence, this study evaluates future breast cancer risk in women who have unequivocally benign lesions. In contrast, Khan et al 18,19 performed a cross-sectional study in which benign epithelium from cases with concurrent breast cancer was contrasted with that of cancer-free controls. These investigators found higher levels of ER expression in the benign epithelium of cases compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Only 10-20 % of cells are ERα-positive in normal resting human mammary glands [40][41][42]. This percentage increases in proliferative benign disease, which is often associated with atypical low-grade ductal carcinoma in situ (DCIS).…”
Section: E2 Signaling In Breast Carcinogenesismentioning
confidence: 99%